1993
DOI: 10.2466/pms.1993.76.3c.1155
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Evaluation of Physical Attractiveness Ideals for Male and Female Body Builds

Abstract: The purposes of this research were (1) to explore gender differences in the evaluation of physical attractiveness stimuli developed to represent commonly occurring real builds, (2) to identify observers' concepts of physical attractiveness ideals promoted by the media, and (3) to begin cross-validation of these stimuli as representations of observers' concepts of ideal physical attractiveness for male and female builds. Responses included (1) open-ended descriptions of ideal male and ideal female build, (2) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…Our findings suggest that contemporary American men display substantial body dissatisfaction and that this dissatisfaction is closely associated with depression, measures of eating pathology, use of PESs, and low self-esteem. These findings reinforce the speculations of many theorists that today's men are laboring under increased societal and media pressures to meet an ever more unrealisticbody ideal (Brodie et al, 1991;Davis, 1985;Dibiase & Hjelle, 1968;Dolan et al, 1997;Guy et al, 1980;Herzog et al, 1991;Mishkind et al, 1986;Salusso-Deonier et al, 1993;Staffieri, 1967;Thompson & Tantleff, 1992;Tucker, 1982).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings suggest that contemporary American men display substantial body dissatisfaction and that this dissatisfaction is closely associated with depression, measures of eating pathology, use of PESs, and low self-esteem. These findings reinforce the speculations of many theorists that today's men are laboring under increased societal and media pressures to meet an ever more unrealisticbody ideal (Brodie et al, 1991;Davis, 1985;Dibiase & Hjelle, 1968;Dolan et al, 1997;Guy et al, 1980;Herzog et al, 1991;Mishkind et al, 1986;Salusso-Deonier et al, 1993;Staffieri, 1967;Thompson & Tantleff, 1992;Tucker, 1982).…”
Section: Discussionsupporting
confidence: 86%
“…& Lacey, 1987;Guy, Rankin, & Norvell, 1980;Herzog et al, 1991;Salusso-Deonier, Markee, & Pedersen, 1993;Staffieri, 1967;Thompson & Tantleff, 1992;Tucker, 1982). As noted in earlier studies, the striking gulf between men's actual and desired muscularity may reflect societal and media pressures on modern men to be ever more muscular .…”
Section: Olivardia Pope Borowiecki and Cohane 116mentioning
confidence: 91%
“…John (2003), heterosexual men now feel pressure to be ''metrosexual,'' a term recently coined for heterosexual men who devote considerable attention to their physical appearance and clothing. These changes have led some theorists to argue that, similar to the unrealistically thin female body ideal, the media has created physical ideals for men that are impossible to achieve (Salusso-Deonier, Markee, & Pedersen, 1993). In fact, research suggests that heterosexual men are becoming increasingly dissatisfied with their physical appearance Frith & Gleeson, 2004;Zelman, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…Men are increasingly subject to articles and advertising in magazines, and to role models in films and on television, that promote images of an ideal male physique that is muscular, mesomorphic, and sharply defined (e.g., McCreary & Sasse, 2000;Morrison et al, 2003;Morry & Staska, 2001;Pope, Olivardia, Gruber, & Borowiecki, 1999). As with the thin ideal for women, such a physique is impossible for most men to attain (Salusso-Deonier, Markee, & Pedersen, 1993). For example, Pope et al's (1999) analysis of the evolution of male action toys concluded that if one contemporary toy (the GI Joe Extreme) was life-size, its biceps would be larger than any bodybuilder could possibly attain.…”
mentioning
confidence: 98%